Kontribusi Nilai-Nilai Pancasila sebagai Landasan dalam Membangun Nilai Karakter Peserta Didik di Sekolah Dasar - Putri Rachma Mawadha; Rizki Alfiana; Respa Yulifianti; Rahmah Sr; Trendi Mahendra; Destrinelli Destrinelli; Muhammad Sofwan (Departement of Mathematics Education, 2024)
Pancasila education is an important factor in shaping national character. In this context, this research aims to find out how to apply Pancasila values ​​in developing the character of elementary school students who are intelligent, creative and have noble personalities. Pancasila as an ideology has an important role in building the identity of Indonesian society. Therefore, Pancasila must be understood and instilled in the nation through the values ​​contained in each point of Pancasila. The research method uses a qualitative approach with literature study. Research data sources are taken from scientific journals, electronic books and other sources. The research results show that the application of Pancasila values ​​can shape the personality of elementary school students through integration in learning and accompanying habits based on teacher direction. Character education from Pancasila needs to continue to be applied in the world of education, especially at the first level of education, especially elementary schools, because with this the quality of Indonesia in the future will be better.